2018
DOI: 10.1016/j.scriptamat.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of liquid feeding during solidification of a steel

Abstract: Sufficient liquid feeding under constrained solidification conditions like, those experienced in welding and casting, is vital to avoid solidification cracking. We present the results of unique in-situ experimental observations of liquid feeding in a solidifying steel melt pool. Liquid feeding was observed in the inter-cellular regions during the terminal stage of solidification. An average liquid flow speed of 450-500 µm s −1 was found. A pressure difference of the order of 10 4 Pa is calculated to cause the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…If the deformation exceeds a certain threshold, separation of the dendrites at the grain boundary can occur. At the terminal stage of solidification, such an opening cannot be compensated by the remaining liquid due to both low permeability and a high solid fraction [5,6]. As a result, solidification cracking occurs.…”
Section: Introductionmentioning
confidence: 99%
“…If the deformation exceeds a certain threshold, separation of the dendrites at the grain boundary can occur. At the terminal stage of solidification, such an opening cannot be compensated by the remaining liquid due to both low permeability and a high solid fraction [5,6]. As a result, solidification cracking occurs.…”
Section: Introductionmentioning
confidence: 99%
“…If the liquid feeding in the inter-dendritic region of the mushy zone is insufficient to compensate for the shrinkage and cumulative deformation of the mushy zone, then the pressure drops below a certain cavitation pressure, voids form and eventually coalesce to form a crack. Agarwal et al [14] observed the solidification process of dual-phase steel in-situ by using a high-temperature laser scanning confocal microscope. Liquid feeding was observed in the inter-cellular regions during the terminal stage of solidification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a higher solute concentration at a GB decreases the permeability of the surrounding mushy zone, which retards liquid feeding. This is particularly detrimental for the already crack prone divergent GBs as liquid feeding alleviates strains associated with solidification shrinkage [145,281]. It is, therefore, evident that microsegregation of solutes to divergent GBs promotes cracking.…”
Section: Elemental Segregation and Tcp Phase Precipitationmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) consists of two additional contributions, the rate of solidification shrinkage (ROS) and the rate of deformation (ROD). A detailed explanation of these terms is provided in [281]. The ROS is defined as…”
Section: Contingency Of Hot Crackingmentioning
confidence: 99%
See 1 more Smart Citation